2019
DOI: 10.1101/522102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel signaling through IRE1α and PERK regulates pancreatic neuroendocrine tumor growth and survival

Abstract: Master regulators of the unfolded protein response (UPR)—IRE1α and PERK— promote adaptation or apoptosis depending on levels of endoplasmic reticulum (ER) stress. While the UPR is activated in many cancers, its effects on tumor growth remain unclear. Derived from endocrine cells, pancreatic neuroendocrine tumors (PanNETs) universally hypersecrete one or more peptide hormones, likely sensitizing these cells to high ER protein-folding stress. For the nearly 1,500 Americans diagnosed with PanNETs annually, surger… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
1
11
0
1
Order By: Relevance
“…Next, we showed that specific inhibition of the IRE1α kinase domain by KIRA8 was coupled with CHOP expression, which could be associated with PERK activation, whereas selective PERK inhibitors conversely decreased the cell viability with the activation of IRE1α. Similar reciprocal effects of IRE1α–PERK were reported in p-NET [ 17 ]. Thus, in neoplasms driven from professional secretory cells, such as myeloma or β-cells, the balance of IRE1α–PERK activities could be essential for the survival and proliferation of tumors under basal ER stress.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Next, we showed that specific inhibition of the IRE1α kinase domain by KIRA8 was coupled with CHOP expression, which could be associated with PERK activation, whereas selective PERK inhibitors conversely decreased the cell viability with the activation of IRE1α. Similar reciprocal effects of IRE1α–PERK were reported in p-NET [ 17 ]. Thus, in neoplasms driven from professional secretory cells, such as myeloma or β-cells, the balance of IRE1α–PERK activities could be essential for the survival and proliferation of tumors under basal ER stress.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, we reported that KIRA8 led to the reciprocal hyperactivation of PERK and apoptotic signaling, halting tumor growth and survival during mild ER stress in pancreatic neuroendocrine tumors (p-NET) [ 17 ]. Surprisingly, KIRA8 increased the PERK-related CHOP mRNA expression in a dose-dependent manner in IM-9 cells, as shown in p-NET ( Figure 2 F).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this notion, human PanNETs were found to have elevated ER stress markers (eg, BiP) and upregulation of homeostatic outputs of the IRE1a and PERK arms of the UPR. 53 More important, rat insulinoma INS-1 cells (a well-established PanNET model) grown in culture have low levels of ER stress and UPR activation; however, the same cells grown in mice as xenografts show marked up-regulation of the UPR, demonstrating that these tumor cells face unique challenges to ER proteostasis in vivo (eg, hypoxia and nutrient deprivation). As such, although loss of IRE1a or PERK had little effect on the growth of INS-1 cells in culture, it markedly halted their ability to form tumors in vivo.…”
Section: The Role Of the Upr In Neoplasms Of Professional Secretory Cellsmentioning
confidence: 99%
“…delivery of the best compound from this series (compound 18 or kinase-inhibiting RNase attenuator 8) showed efficacy in preclinical models of myeloma and pancreatic neuroendocrine tumors. 46,53 A team at GlaxoSmithKline (Brentford, UK) developed highly potent and selective inhibitors of PERK's kinase domain, including GSK2606414 and GSK2656157. 111 Oral administration of GSK2606414 leads to therapeutic doses in the central nervous system and protects against preclinical models of neurodegeneration.…”
Section: The Impact Of the Upr On Tumor Immunitymentioning
confidence: 99%
“…The result showed that those mRNAs were enriched in endoplasmic reticulum (ER) stress. Study had shown that both ER stress and fold-protein response are up-regulated in pancreatic neuroendocrine tumors, which can be used as therapeutic targets for pancreatic tumors [32,33]. Moreover, these mRNAs were also enriched in the response to the nutrient levels pathway and peptide metabolic process pathway.…”
Section: Discussionmentioning
confidence: 99%